A novel ionically crosslinked gel polymer electrolyte as an ion transport layer for high-performance electrochromic devices. Issue 13 (19th March 2019) - Chen, Wanyu; Zhu, Caizhi; Guo, Le; Yan, MengYing; Wu, Lili; Zhu, Bo; Qi, Chenjie; Liu, Siyuan; Zhang, Heng; Peng, Yong
Abstract : In this study, a novel ionically crosslinked gel polymer electrolyte (PADA gel electrolyte) with a transmittance of more than 97% was successfully fabricated and applied in electrochromic devices (ECDs) as an ion transport layer. Abstract : In this study, a novel ionically crosslinked gel polymer electrolyte (PADA gel electrolyte) with a transmittance of more than 97% was successfully fabricated and applied in electrochromic devices (ECDs) as an ion transport layer. The PADA gel-based ECDs (PECDs) exhibited the large optical modulation of 61% at 660 nm, the high coloration efficiency of 78.7 cm 2 C −1, and a good memory effect. The shortest colored time ( t c ) and bleached time ( t b ) of the PECD were 7.5 s and 8.5 s, respectively, due to high Li + mobility of the PADA layer. The ionic conductivities of the PADA gel electrolyte are 1.33 × 10 −2 S cm −1 and 0.56 × 10 −2 S cm −1 at 25 °C and −10 °C respectively, since its conductive behavior is similar to that of liquid electrolytes. The PECDs showed good cycling durability and long-term stability, which is attributed to the stable structures of the PADA gel electrolyte.